HAKIKAT WUJUD: SEBUAH KLASIFIKASI - Husnul Khatimah (LP2M Universitas Ibrahimy, 2018)
When traced by human thoughts, everyone agree that everything that exists do not exist by itself, except for a small part which according to reason, may exist without going through intermediaries. Therefore, any original object that can be transformed into various forms, become these origins have special traits and characteristics, and can be changed to another form. For example water. Water rises into the air into clouds then drops to rain, and winter to snow that is at a time becomes gas. Al-shahrastani said that in the opinion of